Problems of gas exhaust ducts protection of waste incineration plants - Fialko, N.; Navrodska, R.; Shevchuk, S.; Gnedash, G.; Sbrodova, G. (Energy and Automation, 2025)
The results of the analysis the thermal and humidity state at the chimney orifice of waste incineration plant equipped with a heating boiler and a heat recovery system to increase the efficiency of solid household waste (SHW) heat recovery are presented. In the heat recovery system implements waste gases deep cooling and heating of combustion air and return heat-network water before it enters the boiler. This combined use of recovered heat allows increasing the boiler’s efficiency by 6 ÷ 10 %. Two thermal methods are used to prevent condensate formation in the boiler’s exhaust ducts and chimney: mixing air heated in the heat recovery system into the waste gases (air method) and the method of chimney external thermal insulation. The initial data for calculations were taken in the practical range for the combustion of 5 t/h of household waste from the experience of using the "Energia" plant (Kyiv). The calculations were performed in different operating modes of the heat recovery system during the heating period, namely, at inlet air temperatures ranging from -20 to +10 °C and exhaust gas temperatures and moisture content of 250, 200 °C and 150, 200 g/kg of dry gases, respectively. The thermal and humidity parameters (temperature and dew point) of the waste gases, as well as the temperature of the inner surface in the last section of the gas exhaust duct of the waste incinerator - at the chimney orifice were determined. It has been established that under the considered conditions, the use only the air method does not prevent condensation at the chimney orifice in some operating modes of the waste incineration boiler plant. Therefore, to prevent condensation in this chimney, it is proposed to insulate its external surface. The research results show that under the conditions of the combined use of the proposed thermal methods (air and thermal insulation), it is possible to prevent condensation in all operating modes of the considered waste incineration plant. Key words: waste incineration plants, waste gases, chimneys, thermal methods to prevent condensation